Strength behaviour of silica aerogel/thermoset polymer with reinforced fibre-metal laminate composites for aero-engine firewall - Mohammed, I.; Abu Talib, A. R. (Aeronautical and Astronautical Society of the Republic of China, 2020)
The study deals with the mechanical and impact properties based on tensile, compressive, flexural and impacts strength of three composites of aluminium alloy 2024-T3, kenaf fibre and three types of silica aerogel (Hamzel®, Enova® IC3100 and GEA^(TM) 0.125). The main aim of this study is to produce an eco-friendly composites and investigate the mechanical and impact properties of kenaf fibre-metal laminate with different types of silica aerogel/epoxy coating. The composites were made from metal, natural fibre, silica aerogel and epoxy resin/hardener. The mechanical test was conducted using universal testing machine that uses the ASTM standard and the impact test conducted using a helium gas gun tunnel. The result of mechanical properties test shows an improvement in the strengths where Hamzel® metal laminate shows higher values of 10-20% tensile strength and 13-30% tensile modulus than Enova® IC3100 and GEA^(TM) 0.125 metal laminate composites respectively. There are negligible differences among the composites in terms of compressive strength and modulus, while a little difference was recorded on flexural strength and modulus of the three composite with Enova® IC3100 metal laminate composites having the highest value due to the properties of silica aerogel used. For the impact strength and specific perforation energy, there is little difference in the entire composite with Enova® IC3100 metal laminate composites as the most impact strength. The study shows that application of aerogel on metal and reinforced fibre will produced a high strength composite that can be used to substitute the synthetic fibre components in aircraft, automobile and in other component for industrial purposes.